2018
DOI: 10.3390/colloids2030029
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Forces Are Relevant to Bacteria-Nanoparticle Interactions: Pseudomonas putida Capture Efficiency by Using Arginine, Cysteine or Oxalate Wrapped Magnetic Nanoparticles

Abstract: Size, shape and surface characteristics strongly affect interfacial interactions, as the presented among iron oxide nanoparticles (NPs) aqueous colloids and bacteria. In other to find the forces among this interaction, we compare three types of surface modified NPs (exposing oxalate, arginine or cysteine residues), based on a simple synthesis and derivation procedure, that allows us to obtain very similar NPs (size and shape of the magnetic core). In this way, we assure that the main difference in the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
0
9
2
Order By: Relevance
“…This behavior can be observed in Figure 4B, where many bacteria was observed at the surface of the MNPs, thus demonstrating the potential of this system for bacterial enrichment from samples. The capture efficacies here reported are higher than the values previously described 27,49–51 …”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…This behavior can be observed in Figure 4B, where many bacteria was observed at the surface of the MNPs, thus demonstrating the potential of this system for bacterial enrichment from samples. The capture efficacies here reported are higher than the values previously described 27,49–51 …”
Section: Resultscontrasting
confidence: 71%
“…Arg@MNPs showed an efficacy superior to 90% in capturing E. coli ATCC®15597 and Bacillus subtilis from water samples 21 . Another study with the same coated MNPs showed a capture efficacy of 95% for Pseudomonas putida 27 . The use of H‐Coll@MNPs has potential to target microorganisms expressing adhesins; however, its use for bacterial capture was never described.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting binding behavior of cysteine on the nanoparticle surface deduced from the spectra is the formation of cystine, as already observed in similar nanomaterials 52,53 and indicated by the XRD results. Indeed, the bands at 2581 (D), 847 (E), 676 (F) and 540 cm −1 (H) are characteristic of symmetric NH 3 + stretching, NH 3 + rocking, C-S and S-S stretching of cystine, respectively [54][55][56] . The formation of cystine is further demonstrated by SER measurements (Figure 4), where the strong characteristic S-S vibration at 500 cm −1 is observed 57,58 .…”
Section: Samplementioning
confidence: 99%